Inklusi dan Ekslusi Sosial dalam Iklan Televisi : Analisis Wacana Kritis pada Iklan Sampo Pantene - M. Dwi Ananda; Melia Lukluatul Mila; Niken permata Putri; Anas Malik (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2024)
This study aims to analyze the representation of social inclusion and exclusion in television advertisements, focusing on a specific shampoo advertisement. Advertisements play a significant role as a medium of mass communication, often conveying implicit messages related to social and cultural values. The research method used is descriptive qualitative with a critical discourse analysis approach based on Norman Fairclough's model. Data in the form of television advertisement clips were analyzed through the dimensions of text, discourse practice, and social practice to uncover how visual and narrative elements in advertisements promote or discriminate against certain groups. The findings reveal that the shampoo advertisement reflects patterns of social exclusion towards minority groups through stereotypical portrayals while simultaneously emphasizing social inclusion for dominant groups through a homogenized ideal of beauty. The implications of this study highlight the importance of a critical approach to the production and consumption of advertising media to create a more inclusive and equitable communication space.